2021
DOI: 10.1093/mnras/stab093
|View full text |Cite|
|
Sign up to set email alerts
|

Dark matter-deficient dwarf galaxies form via tidal stripping of dark matter in interactions with massive companions

Abstract: In the standard ΛCDM (Lambda cold dark matter) paradigm, dwarf galaxies are expected to be dark matter-rich, as baryonic feedback is thought to quickly drive gas out of their shallow potential wells and quench star formation at early epochs. Recent observations of local dwarfs with extremely low dark matter content appear to contradict this picture, potentially bringing the validity of the standard model into question. We use NewHorizon, a high-resolution cosmological simulation, to demonstrate that sustained … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
47
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 54 publications
(51 citation statements)
references
References 109 publications
4
47
0
Order By: Relevance
“…Carlsten et al 2020;Meneghetti et al 2020) and/or the DM deficiency of associated satellite galaxies (e.g. Ogiya 2018;Jackson et al 2021).…”
Section: S U M M a Ry A N D Discussionmentioning
confidence: 99%
“…Carlsten et al 2020;Meneghetti et al 2020) and/or the DM deficiency of associated satellite galaxies (e.g. Ogiya 2018;Jackson et al 2021).…”
Section: S U M M a Ry A N D Discussionmentioning
confidence: 99%
“…mass fractions as low as ours: three members of our sample have dark-matter mass fractions below 10% and one has only 1% of its mass in dark matter -rendering them almost dark-matter free galaxies. See the Methods Section for work by other groups 5,[12][13][14][15][16][17][18][19][20][21] . One possible explanation is that our simulation has the distinct advantage in being able to model the small-scale (∼ 20 pc) interstellar medium of individual galaxies within a cosmological region (∼ 20 Mpc) large enough to contain several massive groups of galaxies.…”
Section: Starsmentioning
confidence: 99%
“…Simulations by other groups. The identification of galaxies lacking dark matter in cosmological simulations has been a challenge [12][13][14][17][18][19][20] . Whilst many of these studies have shown that galaxies can be produced with dark matter fractions lower than typical, the great majority of them do not produce galaxies below the 1 : 1 line on the M dm − M ⋆ plane (Figure 2).…”
Section: Starsmentioning
confidence: 99%
See 2 more Smart Citations